Label-free and enzyme-free detection of microRNA based on a hybridization chain reaction with hemin/G-quadruplex enzymatic catalysis-induced MoS2 quantum dots via the inner filter effect. Issue 2 (12th December 2019) - Ge, Jia; Qi, Zhangyu; Zhang, Liangliang; Shen, Xueping; Shen, Yanmei; Wang, Weixia; Li, Zhaohui
Abstract : A new label-free, enzyme-free, and specific strategy for the assay of microRNA has been developed based on a hybridization chain reaction with hemin/G-quadruplex enzymatic catalysis-induced MoS2 quantum dots via the inner filter effect. Abstract : A new simple, sensitive and specific strategy for microRNA analysis has been described based on a hybridization chain reaction with hemin/G-quadruplex enzymatic catalysis-induced MoS2 quantum dots via the inner filter effect. The target microRNA triggers the hybridization chain reaction between two DNA probes to generate long dsDNA with many hemin/G-quadruplex DNAzymes in the presence of hemin. With the assistance of H2 O2, the produced hemin/G-quadruplex DNAzyme could oxidize o -phenylenediamine (OPD) to 2, 3-diaminophenazine (DAP) directly, resulting in the fluorescence quenching of MoS2 quantum dots via the inner filter effect. As an example, the fluorescence response of MoS2 quantum dots is linearly related with the logarithm of the microRNA let-7a concentration with a detection limit of 42 fM. The proposed label-free assay has promising potential to be applied in practical diagnosis.